2019
DOI: 10.1080/1478422x.2019.1658427
|View full text |Cite
|
Sign up to set email alerts
|

Empirical models for long-term localised corrosion of cast iron pipes buried in soils

Abstract: Empirical models are proposed for the progression of maximum depth of localised corrosion of cast iron pipes, based on data for pipes buried in 67 different backfill clay and sandy soils for up to 129 years. Early corrosion increases with increased inhomogeneity of the backfill soil and with greater availability of free water at the soil-pipe wall interface. Longer term corrosion is correlated with free water availability and occurs at a much slower rate. In most cases, the free water is fresh, oxygenated rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…And thus the CR measured under these conditions can be expected to be lower than the long-term rate of localised corrosion penetration of cast iron pipes buried in silty, light and medium clays (which have CR in the range 66-73 μm y −1 ), when the burial environment is less dense since backfill soils are prone to permeation by rainwater, run-of water, etc. This would lead to a great availability of free water at the soil-metal wall interface and therefore to higher CR [52]. The effect of the water content observed in the present study is consistent with that reported earlier by Petersen et al for the effect of moisture content on the corrosion of mild steel buried in clay soils (many studies are available for sandy soils and loams, while few recent studies are for clay soil) [53].…”
Section: Discussionsupporting
confidence: 92%
“…And thus the CR measured under these conditions can be expected to be lower than the long-term rate of localised corrosion penetration of cast iron pipes buried in silty, light and medium clays (which have CR in the range 66-73 μm y −1 ), when the burial environment is less dense since backfill soils are prone to permeation by rainwater, run-of water, etc. This would lead to a great availability of free water at the soil-metal wall interface and therefore to higher CR [52]. The effect of the water content observed in the present study is consistent with that reported earlier by Petersen et al for the effect of moisture content on the corrosion of mild steel buried in clay soils (many studies are available for sandy soils and loams, while few recent studies are for clay soil) [53].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, despite the various developments, underground structural failures continue to occur [ 1 , 2 , 3 ]. Here, the corrosion of metallic infrastructures in underground soil is a major issue that presents numerous safety and economic concerns [ 4 , 5 , 6 , 7 , 8 ]. In short, pipelines can be damaged by corrosion, which can lead to the failure of the structures within a soil environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the widely accepted and have been used classification methods to evaluate the corrosive nature of the soil to buried-metallic pipelines are ASTM [23][24][25], NACE [26,27] and ANSI/AWWA [28,29]. The ASTM and NACE systems are practiced previously to assess the degree of soil corrosivity to the buried-metallic pipelines [30][31][32][33][34][35][36]. In both the ASTM and NACE systems, the electrical conductivity/resistivity of soils is believed as the most important parameter for the evaluation of the buried-pipe corrosion, although the effects of other physicochemical soil parameters take account of less significance.…”
Section: Introductionmentioning
confidence: 99%